(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The purpose of this study is to describe the implementation of multiple intelligence-based “Fraction” textbooks through Discovery Learning for elementary school students. This implementation is based on learning outcomes tests, student activities and student response questionnaires. This research is included in the implementation phase of the ongoing ADDIE development model. This study uses a descriptive quantitative approach. The subjects in this study were 5th grade students of SDI A-Education with a total of 20 students. The technique used is a test technique to determine the improvement of tests for mathematical logical intelligence, linguistics, and visual spatial, observation techniques to observe student activities and questionnaire techniques to determine student responses to the use of textbooks and learning models. From the results of the study obtained data that through the calculation of the N-Gain Score, it was found that there was an increase in test results before and after learning for the three intelligences with each getting the "Medium" category. Based on the observations of student activities, the three activities that are mostly carried out by students are in accordance with learning, namely discussing/asking between students/teachers, presenting their work and drawing conclusions from procedures/concepts. For the student response questionnaire, the results were in the "Good" category.